Port of Koper as Key Company of the Slovenian Transport Logistic Cluster - Igor Trupac; Jurij Kolenc (Promet - Traffic&Transportation, 1970)
Today, the countries of Central andEastemEurope (CEE)have developed into a fast growing and promising part of Europe.The vision of the management of the Port of Koper is tobecome the most important logistic centre for these countries.In the future the North Adriatic region will have to cope withfurther challenge, i. e. an increasing presence of the Asian Pacificeconomies on the European continent and in the CEEcountries in particular. For the traffic flows from this source,the North Adriatic is, from the geo-transport aspects the mostconvenient seaway/ route.It was for this reason that the Port of Koper as the key companyjoined a pilot project- STLC (Slovenian transport logisticcluster) as a stakeholder. The main purpose of the STLC is topromote the Slovenian transport route using the Port of Koperas the focal point.This paper aims to: (I) review the current state of the developmentof Slovenian transport logistic cluster, (JJ) assess thepotential benefits of such a cluster for the Port of Koper (Ill) introduceinitial presentations, experiences and results.